Prognostic Value of Concurrent Expression of C-MYC and BCL2 in Intravascular Large B-Cell Lymphoma: A 10-Year Retrospective Study - Paisarn Boonsakan (2020)
© 2020 Paisarn Boonsakan et al. Background. Intravascular large B-cell lymphoma (IVLBCL) is a variant of extranodal diffuse large B-cell lymphoma (DLBCL), characterized by the presence of a B-lymphoma cell in the lumina of small blood vessels or capillaries. Due to its extremely variable clinical manifestations, IVLBCL typically results in a delayed diagnosis and poor disease prognosis. Skin biopsy, particularly random skin biopsy, has shown a potential role in the diagnosis of IVLBCL. However, information of clinicopathological features in patients with IVLBCL diagnosed by skin biopsy is limited. Objectives. To study the clinicopathological features in relation to immunohistochemical features and to identify prognostic factors in IVLBCL patients diagnosed by skin biopsy. Materials and Methods. Clinical characteristics; laboratory, histological, and immunohistochemical findings; and therapeutic response of all biopsy-confirmed IVLBCL patients during the years 2008-2017 were retrospectively reviewed. Results. The mean age was 67.4 (±9.8) years. Fever was the most common presenting symptom, accounting for 64.7%. Cutaneous and bone marrow involvement was found in 23.5% and 35.3% of patients, respectively. Patients receiving R-CHOP showed more favorable therapeutic outcome. C-MYC/BCL2 double expressors showed significantly higher incidence rate to mortality compared with nondouble expressors (p=0.042). One-year and two-year overall survival rates were 67.2% and 53.8%, respectively. Conclusions. Skin biopsy is an effective diagnostic method for IVLBCL. Concurrent expression of C-MYC and BCL2 may be a useful prognostic indicator and should be performed in order to predict the prognosis in IVLBCL patients.